18F‐PI‐2620 tau‐PET in corticobasal syndrome (ActiGliA cohort): Neuroimaging: Other neurodegenerative disorders. (7th December 2020) - Brendel, Matthias; Palleis, Carla; Prix, Catharina; Finze, Anika; Boetzel, Kai; Danek, Adrian; Höllerhage, Matthias; Beyer, Leonie; Sauerbeck, Julia; Rauchmann, Boris; Stephens, Andrew W; Drzezga, Alexander; et al.
Abstract: Background: The pathology of Corticobasal syndrome (CBS) is characterized by 4‐repeat (4R)‐tau aggregation in Corticobasal Degeneration (CBD) and Progressive Supranuclear Palsy (PSP) in ∼50%, or by (3/4R)‐tau aggregation in Alzheimer's disease (AD) in ∼25% of patients. The second generation tau‐PET ligand 18 F‐PI2620 showed high affinity to 3/4R‐tau in AD and also revealed affinity to 4R‐tau pathology. The aim of this study was to investigate 18 F‐PI2620 in patients with CBS that are part of the interdisciplinary AD study "Activity of Cerebral Networks, Amyloid and Microglia in Aging and Alzheimer's Disease (ActiGliA)". Method: ActiGliA comprises a comprehensive clinical assessment, multimodal prospective imaging in vivo and fluid biomarker analyses. Thirty‐five patients (70±8y) with probable or possible CBS according to MDS‐PSP or Armstrong‐criteria underwent 18 F‐PI2620 PET together with ten age‐matched healthy‐controls. Distribution volume ratios (DVR, 0‐60 min) of subcortical and cortical brain‐regions were generated using cerebellar reference tissue. DVR‐data were quantitatively and visually compared between CBS and healthy‐controls. Regional 18 F‐PI2620 binding was compared with clinical severity (PSP rating scale, PSPRS), and disease duration. Amyloid‐PET served for assessment of β‐amyloid status. Result: 26% (9/35) of CBS patients (PSPRS: 25±13) were amyloid‐positive. Overall, a visually discernible 18 F‐PI2620 was observed in 26 subjects (74%) and in 89% of amyloid‐positive CBS patients. Significantly elevated 18 F‐PI2620 DVR was observed in the whole group of CBS patients versus healthy controls in the putamen, globus pallidus and subthalamic nucleus (Cohen's d: 1.19/ 1.44/ 1.11, all p<0.01). The cortical signal was higher in amyloid‐positive when compared to amyloid‐negative CBS patients (DVR: 1.05±0.15 vs. 0.95±0.05, p=0.005, Figure 1). Cortical binding in CBS was heterogeneous (positive in 49%; 17/35, Figure 2). Asymmetry of PET tracer uptake matched the contralateral clinical dominance in 94% of CBS cases. 18 F‐PI2620 binding showed a correlation with disease severity in the globus pallidus after controlling for age, sex and β‐amyloid‐status (R=0.426, p=0.021). Conclusion: The application of 18 F‐PI2620 in the ActiGliA study shows that 18 F‐PI2620 is a potential biomarker for evaluation of CBS, facilitating detection of heterogeneous neuropathology and variable cortical and subcortical deposition sites, which could serve for monitoring disease status, progression, and target engagement.